DAMPAK LEADERSHIP & CORPORATE SOCIAL RESPOSIBILITY TERHADAP TALENT RETENTION DI INDUSTRI MANUFAKTUR - Antonio Tantra Wijaya; Alden Nelson; Bernard Bernard; Edwin Edwin; Erick Erick; Wenny Wenny (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine the impact of leadership and corporate social responsibility on talent retention. In the world of work, the term talent retention is no stranger because companies want to retain the best and most talented employees. Therefore, talent retention is very important for a company. The method used in this analysis is a qualitative method by observing through case studies and documentation. The results of the analysis are that leadership and corporate social responsibility have a positive and significant impact on Talent Retention. A company with a good leadership style will influence employees' decisions to stay in the company. Companies that have a good CSR program will also influence employees' decisions to stay with the company because a good CSR program will have a positive impact and help increase employee productivity, skills and motivation so that the company's talent retention will also increase. The advice that can be given is that companies must have a good leadership style and CSR program so that the company's talent retention can run well.